TAX INCENTIVE LAWS AS AN ALTERNATIVE IN FIGHTING CHILD CRIMINALITY (CIPEEX, 2024)
The insertion of young people and children into crime is a problem that must be addressed by various government spheres, as it is a social problem that directly affects the fundamental rights of children and adolescents. This work aimed to study the main characteristics of the involvement of young people and children in crime, pointing out how the Tax Incentive Law can contribute to reducing this number, and promoting improvements for this population. Based on the data collected, the main causes that lead to the involvement of children and young people in crime mainly include social issues, such as lack of access to education, leisure and culture; as well as economic issues, such as low family income. Through the Tax Incentive Law, government and entities, such as NGOs, can promote actions that bring these young people away from crime into their spaces, bringing education, sport, cultural activities to their reality, allowing these individuals to experience other spaces beyond their own reality. This absorption by these entities reduces the factors that can lead these children to crime, allowing other possibilities to emerge throughout their lives. However, it should be noted that greater commitment is needed on the part of government officials so that the tax incentive reaches these institutions, so that they can then put their work into practice in the best possible way